Vulnerability Assessment of Vehicle Keyless Entry Systems Using the PTES Methodology - Ulil Akbar; Muhammad Abdul Aziz; Donna Setiawati; Yusuf Eko Rohmadi (Postgraduate, University of Mataram, 2025)
The growing adoption of keyless entry systems in motor vehicles introduces new challenges in the security of radio-based communication. This study aims to identify and evaluate the vulnerability level of the keyless entry system on the Honda PCX 150 motorcycle against two types of man-in-the-middle-based attacks: replay attack and relay attack. Using the Penetration Testing Execution Standard (PTES) methodology, the study establishes a seven-stage testing procedure, from pre-engagement to reporting. Experiments were conducted using Flipper Zero as the main device, supported by GNU Radio, Software Defined Radio (SDR), and Universal Radio Hacker (URH). Each type of attack was tested 25 times. The results showed a 44% Success rate for the replay attack and 48% for the relay attack. Further analysis revealed that Success occurred not only on repeated frequencies but also on single-occurrence frequencies, with effectiveness rates of 50% and 45%, respectively. These findings indicate the absence of security mechanisms such as rolling code, time or location-based validation, and frequency hopping, allowing intercepted signals to be accepted by the vehicle. The study concludes that the Honda PCX 150's keyless entry system has significant security gaps, potentially exploitable using passive tools. It recommends the implementation of dynamic authentication mechanisms and cryptographic technologies to enhance the security of vehicular radio signal transmissions.